PEMODELAN DAYA DUKUNG PEMANFAATAN PULAU SAPUDI DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Firman Farid Muhsoni (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2016)
MODELLING OF UTILIZATION CARRYING CAPACITY OF SAPUDI ISLAND USING GEOGRAPHIC INFORMATION SYSTEMSumenep Regency has natural resources in the form of coral reefs and mangrove which are potential to be exploited. The number of islands with names in Sumenep regency as many as 106 islands. This study was aimed to mapping the land physical parameters used for modeling the carrying capacity utilization and assessment of Sapudi Island. The method used was the geographic information system modeling for ecotourism suitability model using index approach. Coral reefs in Sapudi Island was found about 1,544 ha. The condition of coral reefs in Sapudi Island taken using Underwater Photo Transect method was 25.9% live coral and dead coral was 71.55%. Water temperature conditions were between 30,1-30.5 0C, pH were 6.8-7.1, salinity were 25-30 0/00, dissolved oxygen were 4.6-6.6 mg/l and water clarity of 100%. Carrying capacity utilization of Sapudi Island for diving ecotourism was about 1,947 people/day, while for snorkeling ecotourism was 2,283 person/day.Keywords: carrying capacity, ecotourism, small island, Sapudi.ABSTRAKKabupaten Sumenep mempunyai sumberdaya alam terumbu karang dan mangrove yang sangat potensial untuk dimanfaatkan. Jumlah pulau yang mempunyai nama di Kabupaten Sumenep sebanyak 106 pulau. Penelitian bertujuan ini pemetaan parameter fisik lahan yang akan digunakan untuk pemodelan daya dukung pemanfaatan dan penilaian daya dukung pulau Sapudi. Metode yang dipergunakan adalah pemodelan Sistem Informasi geografis untuk kesesuaian ekowisata dengan pendekatan model indeks. Luas terumbu karang di Pulau Sapudi ditemukan mencapai 1.544 ha. Kondisi terumbu karang di Pulau Sapudi dengan metode Transek Foto Bawah air untuk karang hidup 25,9 %, karang mati 71,55 %. Kondisi suhu air 30,1- 30,5 0C, pH 6,8-7,1, salinitas 25-30 0/00, Oksigen terlarut 4,6-6,6 mg/l dan kecerahan 100%. Daya dukung pemanfataan Pulau Sapudi untuk ekowisata selam 1.947 orang/hari, untuk ekowisata snorkeling 2.283 orang/hari.Kata kunci: daya dukung kawasan, ekowisata, pulau kecil, Sapudi.